Selective Synthesis of α‐Alkoxy Enones by α‐Addition of Alcohols to Alkynones Using 1, 1, 1, 3, 3, 3‐Hexafluoroisopropanol and PPh3 as Co‐catalysts. Issue 47 (13th December 2022) - Li, Xiu‐Ming; Yang, Jing‐Kui
Abstract: α‐Alkoxy enones are quite useful building blocks in organic chemistry. The existing methods for syntheses of these compounds remain somewhat limited. Over the past years, nucleophilic phosphine catalysis has emerged as a practical and powerful tool for constructing diverse molecules with the advantages of environmental‐friendly, metal‐free, and mild reaction conditions. Meanwhile, alkynone is easy to prepare, can undergo a variety of reactions, and is a commonly used substrate for organic synthesis. α‐Addition of alcohols to alkynones is a direct way to construct α‐alkoxy enones. In this study, it was delightful to find that using PPh3 (10 mmol %) and 1, 1, 1, 3, 3, 3‐hexafluoroisopropanol (HFIP) (20 mmol %) could redirect from β‐addition to α‐addition. With this approach, a variety of α‐alkoxy enones could be obtained directly with good yields and regioselectivity. Under optimal conditions, the generality of the reaction was investigated. Substrate scope studies showed that the reaction was well tolerated with many alcohols. Mechanistic study is also demonstrated. Abstract : The α‐addition of alcohols to alkynones was demonstrated. A series of α‐alkoxy enones can directly be synthesized in moderate to high yields under mild conditions. Mechanism studies were carried out by various means.